KOMUNIKASI TERAPEUTIK DALAM HIPNOTERAPI PASIEN GANGGUAN KECEMASAN (ANXIETY DISORDER) DI GLOW MIND KLINIK HIPNOTERAPI PEKANBARU - Natalina Pakpahan; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Hypnotherapy is an alternative treatment lie using hypnosis as part of healing process with the aim to uncover the client’s psychological problems applied in Glow Mind Clinic Hypnotherapy Pekanbaru since it’s establishment in 2010 ago. Therapist uses the consultation to find out the cause of the anxiety disorder to determine the suggestion to be implanted in the client’s subconscious mind. Communication is an important part and the main thing in implementing hypnotherapy is therapeutic communication. The purpose of this study was to look at the therapeutic communication phases that were applied in the Glow Mind clinic.The method in this research is qualitative that describes the purpose of research and interpreted interpretively. Informants in this research are Main Therapist, Backup Therapist, Admin and 4 client with purposive technique. Data collection techniques used are observation, interviews and documentation with data validity techniques using extension of participation and triangulation.The results showed that therapists in carrying out therapeutic communication to clients anxiety disorder in Glow Mind Clinic Hypnotherapy Pekanbaru done through several stages. In the pre-interaction phase the therapist collects information about the client and devises a way to build interpersonal relationships with the clients he will face by practicing an attitude of openness, empathy, supportive attitude, positive attitudes and equality that can build the effectiveness of interpersonal communication. In the orientation phase the therapist will familiarize themselves with the client by showing a friendly and open attitude, the goal is to open up each other and build a relationship of trust. At the work phase, the therapist will explore deeper information about the anxiety disorder of the client by implementing some therapeutic communication techniques, such as: listening, silence, giving open questions, repeating and clarifying, focusing, summarizing, informing, offering. In the termination phase, the therapist will give advice to the client to remind suggestions already implanted in the client's unconscious mind.Keywords: therapeutic communication, hypnotherapy, therapist and client